2009
DOI: 10.1007/s00414-009-0351-x
|View full text |Cite
|
Sign up to set email alerts
|

Forensic aspects of post-mortem histological detection of amniotic fluid embolism

Abstract: Amniotic fluid embolism (AFE) continues to be one of the most feared and devastating complications of pregnancy. A reliable diagnosis can be made only upon histological examination. A detection of AFE every now and then has a relevant implication on medico-legal aspects of intrapartum or post-partum maternal death. However, there are only isolated reports in the literature concerning the detection interval of amniotic fluid elements after their transfer into the lungs. The objective of this study was to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 22 publications
2
19
0
1
Order By: Relevance
“…Similarly to other recent publications [46][47][48][49], this manuscript confirms the importance of the histological and immunohistochemical investigations in the routinely medico-legal practise.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly to other recent publications [46][47][48][49], this manuscript confirms the importance of the histological and immunohistochemical investigations in the routinely medico-legal practise.…”
Section: Discussionsupporting
confidence: 91%
“…All four AFE patients had positive staining of the pulmonary vasculature while the control group of four women who died from non-AFE causes did not. A second study of twenty-seven maternal deaths found fetal material in 100% of AFE patients and none in those dying of non-AFE causes [57]. It should be noted that the study findings were problematic since the authors began with the assumption that any fetal material in the maternal vasculature was diagnostic of AFE.…”
Section: Laboratory Diagnosis Of Afementioning
confidence: 99%
“…Deaths related to amniotic fluid are a classical task in legal medicine and are represented, from one side, by cases of embolism through uterine veins during labor and delivery [25,26] and, from the other side, by its possible aspiration in the airways of the newborn during delivery [27,28]. The aspiration of uncontaminated amniotic fluid has been repeatedly reported to be potentially lethal [9,13,14].…”
Section: Discussionmentioning
confidence: 99%